A mild and efficient method for the deprotection of trimethyl silyl alkynes using sodium ascorbate and copper sulphate - Siddaraj, Ranjith; Ningegowda, Raghu; Shivananju, Nanjunda Swamy; Priya, Babu Shubha (European Journal of Chemistry, 2018)
A competent and fast method for the deprotection of trimethyl silyl group was attained by using cheap, easily accessible, and nontoxic sodium ascorbate in combination with copper sulphate. The method labored was simple and effective for the cleavage of trimethyl silyl group from the protected trimethyl silyl alkynes to their corresponding alkyne derivatives. Wide functional group tolerance, shorter time period, simple procedure and high yields are the striking features of this protocol.